Comparative genetic analysis and pathological characteristics of goose parvovirus isolated in Heilongjiang, China - Yinjie Niu; Lili Zhao; Baihan Liu; Jingli Liu; Fan Yang; Haichang Yin; Hong Huo; Hongyan Chen (Virology Journal, 2018)
Abstract Background Goose parvovirus (GPV) causes acute enteritis, hepatitis, myocarditis and high morbidity and mortality in geese and ducks. GPV H strain was isolated from a Heilongjiang goose farm where the geese were showing signs of hemorrhage in the brain, liver, and intestinal tract. In this study, we explored the genetic diversity among waterfowl parvovirus isolates and the pathological characteristics of GPV H in Shaoxing ducklings. Methods The complete capsid protein (VP) and non-structural (NS) sequences of the isolated H strain were sequenced, and phylogenetic trees of VP and NS were constructed in MEGA version 5.05 using the neighbor-joining method. Three-day-old Shaoxing ducklings were inoculated with GPV and were euthanized at 1, 2, 4, 6, and 8 days post-inoculation (PI), and their organs were removed and collected. The organs of 6-day PI ducklings were fixed in formalin, embedded in paraffin, sectioned for histology, stained with HE and analyzed for pathological lesions. The distribution of the GPV H strain in the tissues of the inoculated ducklings was detected using the polymerase chain reaction (PCR) method. Results Genetic analysis of the NS and VP genes indicated that the H strain was closely related to strains circulating in China during 1999–2014, and the nucleic acid identity of those strains was 98%–99%. Classical symptoms were observed in the inoculated ducklings. GPV remained in many tissues and replicated in a majority of the tissues, leading to histopathological lesions in four tissues. Conclusions We first reported the distribution and histopathological lesions of a Chinese strain of GPV in infected shaoxing ducklings. This H strain was moderate pathogenic for Shaoxing ducklings.